Uji Aktivitas Antibakteri Sabun Transparan Putik Saffron (Crocus sativus L) terhadap Bakteri Staphylococcus aureus - Emmy Wiriandini; Gabena Indrayani Dalimunthe; Minda Sari Lubis; Haris Munandar Nasution (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Transparent soap is a variation of solid bar soap that not only functions to clean dirt but also has a scrubbing function. Transparent solid soap is one of the soap innovations that has become an attractive soap. Saffron also has antibacterial properties due to the presence of flavonoids, tannins and saponins. Flavonoids are compounds that can have anti-inflammatory, anticancer and antioxidant effects, because they can inhibit the formation of free radicals. It has been used traditionally to treat various ailments including depression, cardiovascular disease, menstrual disorders, asthma, insomnia, digestive ailments, bone pain and several other ailments. Saffron pistil juice is made by dissolving in CO₂-free distilled water. Phytochemical screening was carried out on saffron pistil extract. Saffron pistil juice is made in various soap formulas, namely formula I, formula II and formula III. The positive control used was chloramphenicol antibiotic and the negative control was DMSO. There were several tests carried out on Saffron pistil extract in addition to phytochemical screening, namely antibacterial testing on transparent soap with Saffron pistil extract as a soap additive. The results of phytochemical screening showed that the pistil of saffron (Crocus sativus L) contained secondary metabolites, namely: flavonoids, alkaloids, tannins, and saponins. And for the results of the antibacterial activity research also showed that the Saffron pistil extract against transparent soap which can be used as a soap additive, the antibacterial results had a strong inhibition at the average value of formula III which was 20.5 and formula II was 18.4 mm and formula I 16.1 mm, against Staphylococcus aureus bacteria.